Effects of pressurizing timing on air booster vacuum consolidation of dredged slurry. Issue 4 (August 2020) - Anda, Rila; Fu, Hongtao; Wang, Jun; Lei, Huayang; Hu, Xiuqing; Ye, Qiang; Cai, Yuanqiang; Xie, Zhiwei
Abstract: Air booster vacuum preloading is a newly improved method applied in land reclamation projects. Highly pressurized air can provide an additional pressure difference between the prefabricated vertical drain (PVD) and injection point, thereby increasing the hydraulic gradient and generating small fractures that can improve the soil permeability and the transmission efficiency of the vacuum pressure. However, with a premature activation time, the pressurized air can create air channels connected to the PVD, which may drastically decrease the vacuum pressure. With a delayed activation time, the strength of the dredged clay may be too high to permit fractures, thus limiting the permeability improvement. In this study, soils with degrees of consolidation (DOCs) of 0%, 40%, 60%, and 80% were selected for testing the efficacy of initial booster activation times in four tests. The results show that the pressurizing groups were more effective in improving the consolidation of soils, and the best effect of the use of air booster is obtained when soil has been consolidated to a DOC of 60%. The lower soils of the pressurized groups showed greater increase rates than those demonstrated by conventional vacuum preloading.